2014
DOI: 10.1089/dna.2014.2469
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptome Analysis and Identification of the Flowering Regulatory Genes Expressed in Leaves of Lagerstroemia indica

Abstract: Flowering time is an important trait for ornamental plants, and flowering regulation has thus been both a focus of and challenge to researchers. Lagerstroemia indica is an important summer flowering tree in China and has been introduced abroad as a key parent of new cultivars; no previous reports have addressed the regulation of flowering time in this species. In this study, 28,567,778 · 2 reads were obtained from leaves of L. indica. A total of 37,325 unigenes were assembled with an average length of 849.56 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Genes conditioning vernalization namely Vrn-A1, Vrn-B1, and Vrn-D1 regulate flowering and maturity in wheat (Iwaki et al, 2002). The effect of Vrn loci on heading and maturity, and grain yield potential are ranked as follows: Vrn-A1 < Vrn-B1 < Vrn- D1 (Zheng et al, 2013; Zhang et al, 2014; Ogbonnaya et al, 2017). This resulted in increased days to heading and grain yield under optimal environments, but decreased grain yield under heat prone environments (Zhang et al, 2008; Kamran et al, 2013b; Ogbonnaya et al, 2017).…”
Section: Use Of Agronomic Traits In Phenotyping Wheatmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes conditioning vernalization namely Vrn-A1, Vrn-B1, and Vrn-D1 regulate flowering and maturity in wheat (Iwaki et al, 2002). The effect of Vrn loci on heading and maturity, and grain yield potential are ranked as follows: Vrn-A1 < Vrn-B1 < Vrn- D1 (Zheng et al, 2013; Zhang et al, 2014; Ogbonnaya et al, 2017). This resulted in increased days to heading and grain yield under optimal environments, but decreased grain yield under heat prone environments (Zhang et al, 2008; Kamran et al, 2013b; Ogbonnaya et al, 2017).…”
Section: Use Of Agronomic Traits In Phenotyping Wheatmentioning
confidence: 99%
“…Breeding strategies to replace the winter-type alleles, especially Vrn - A1 and Vrn - D1 loci associated with late heading times (Zhang et al, 2008), has been recommended to develop early-flowering cultivars for water-limited environments. Zhang et al (2014) reported that the genotypes possessing the Vrn-A1avrn-B1Vrn-D1a loci would result in reduced time to anthesis and improve grain yield potential and kernel number in water-stressed environments. Contrastingly, incorporation of Vrn-D1 is recommended in spring wheat to increase grain yield and improve adaptation to late drought and heat stress tolerance.…”
Section: Use Of Agronomic Traits In Phenotyping Wheatmentioning
confidence: 99%
“…Recently, the advent of NGS-based RNA sequencing (RNA-seq) of transcriptome has provided an opportunity for large-scale discovery and profiling of functional genes involved in diverse biological processes [ 18 , 19 ], such as floral scent biosynthesis in wintersweet [ 20 ], discovery of disease-resistance genes (NBS-LRR genes) in Camelina sativa [ 21 ], biosynthesis and accumulation of lignin in celery [ 22 ] and terpenoid biosynthesis in pitanga [ 23 ]. RNA-seq has also been used for the discovery of genes related to flowering time regulation and flower development in some plant species including bamboo [ 24 , 25 ], Eichhornia paniculata [ 26 ], Lagerstroemia indica [ 27 ], Ipomoea nil [ 28 ] and sweet potato [ 29 ]. However, genome-wide identification of flowering-related functional genes is still lacking in root vegetable crops.…”
Section: Introductionmentioning
confidence: 99%
“…Dwarf crape myrtle cultivars are characterized by a low plant height, a compact plant type, short internodes and abundant mini flowers, and they have been selected for Lagerstroemia breeding programs [ 25 ]. To date, significant progress has been achieved with regard to new varietal breeding [ 26 – 28 ], germplasm evaluations [ 29 ], genetic diversity analyses [ 30 , 31 ], molecular marker development [ 32 , 33 ], genetic linkage map construction [ 34 ] and transcriptome analyses [ 35 , 36 ]. However, an in-depth study has not been conducted on the genetic mechanism underlying dwarf traits.…”
Section: Introductionmentioning
confidence: 99%